(untitled) (Journal of Partial Differential Equations, 2023)
Professor Zhou Yulin was born on February 12, 1923 in Shanghai and passed away on March 2, 2021 in Beijing. As a famous mathematician, he was the deputy director of the Institute of Applied Physics and Computational Mathematics, a member of the Science and Technology Committee of the Chinese Academy of Engineering Physics, and the chairman and honorary chairman of the Chinese Society of Computational Mathematics.